Training needs of practising professional librarians in the Kenyan public university libraries: a critical analysis - Okemwa, Ezra Ondari (MCB University Press, 2000)
Examines the training needs of practising professional librarians in the Kenyan public university libraries. There is a general, but false assumption, in this sector that professional librarians who have attained the minimum professional qualifications need no further training on the job. Many changes have taken place and many more are likely to occur, which are likely to affect the working environment of librarians. Librarians must be trained in preparation for managing such changes. Suggestions for sources of funding are given. The specific training needs of practising librarians are described.
Keywords: On-the-job training; Librarians; Kenya; University libraries